Impact of Nutritional Intervention on Taste Perception—A Scoping Review - Alessandro Micarelli (MDPI AG, 2021)
The aim of the present scoping review was to evaluate the impact of experimental meal loads or observational diet changes/habits on taste tests in both healthy subjects and patients. A systematic search performed in PubMed, Scopus, and Institute for Scientific Information (ISI) Web of Science electronic databases retrieved, respectively 2981, 6258, and 7555 articles from January 2000 to December 2020. A total of 17 articles were included for full-text review. Literature results were stratified according to the observational/interventional approach, the involvement of healthy subjects or patients, the taste test, and the meal/dietary changes. The present scoping review reinforced the notions postulating that certain taste tests (for example focusing on fatty acid, salt, or sugar) might be specifically influenced by the nutritional intervention and that other ones might be susceptible to a wide span of changes beyond the extent of tastant included in the specific food changes. This could also depend on the inhomogeneity of literature trend: The short duration of the intervention or the random type of meal load, unsuitability of the taste test chosen, and the presence of underlying disorders. Future studies for a better comprehension of taste tests reliability in relation to specific food changes are thus to be fostered.